On the evolution of finite and small amplitude waves in non-ideal gas with dust particles - Srivastava S.K.; Chaturvedi R.K.; Singh L.P. (My University, 2025)
The present work concerns with the study of progressive wave solution for the waves of finite and moderately small amplitude in the mixture of the non-ideal gas and dust particles governed by quasilinear hyperbolic system of PDEs. Using the progressive wave method, we derive the transport equation which provides the conditions of the shock formation, and equation to determine the shock strength. Also, it is shown that how the presence of the parameter of non-idealness and mass fraction of dust particles influence the shock formation and shock strength for the planar and non planar cases. We also discuss the consequence of variation in the value of the non-ideal parameter and the mass fraction of small solid dust particles on the evolutionary process of the shock. © 2020 IOP Publishing Ltd.